2020
DOI: 10.1021/jacs.0c08117
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Polycatenation of a Uranium-Based Metal–Organic Cage: Structural Complexity and Radiation Detection

Abstract: The potential applications of metal–organic cages (MOCs) are mostly achieved through specific host–guest interactions within their cavities. Electronic applications would require an effective electron transport pathway, which has been extensively studied in hybrid organic–inorganic materials with extended structures. These properties have not been considered for MOCs because cage-to-cage interactions in these materials have rarely been examined and are challenging to functionalize. We report here a previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 45 publications
1
59
0
Order By: Relevance
“…After a total dose of 20–100 kGy γ irradiation for 7 hours, the PXRD patterns of each crystal after irradiation showed that its frame structure still existed and did not collapse within the radiation intensity determined by the experiment. All these materials had radiation resistance comparable to that of SCU-14, 32 a uranium-based MOF which was irradiated continuously at a cumulative dose of 120 kGy with little change in photoelectric response.…”
Section: Resultsmentioning
confidence: 98%
“…After a total dose of 20–100 kGy γ irradiation for 7 hours, the PXRD patterns of each crystal after irradiation showed that its frame structure still existed and did not collapse within the radiation intensity determined by the experiment. All these materials had radiation resistance comparable to that of SCU-14, 32 a uranium-based MOF which was irradiated continuously at a cumulative dose of 120 kGy with little change in photoelectric response.…”
Section: Resultsmentioning
confidence: 98%
“…Metal–organic frameworks (MOFs), also known as the coordination polymer, are a promising class of porous materials constructed through the self-assembly of organic linkers and metal ions/clusters ( Cui et al, 2018 ; Esrafili et al, 2020 ; Hu et al, 2020 ; Cao et al, 2021 ; Lv et al, 2021 ; Wu et al, 2021 ). Due to the merits of large surface areas, tunable structures, and excellent stability, MOFs have been widely employed in various applications, such as gas storage and separation, sensing, catalysis, and biomedicine ( Wang et al, 2018 ; Zheng et al, 2018 ; Wu S. et al, 2020 ; Cheng et al, 2020 ; Hu E. et al, 2021 ; Hu M.-L. et al, 2021 ; Esrafili et al, 2021 ; Li et al, 2021 ; Zhou et al, 2021 ). Recently, several powder-form MOFs have been explored to remove and detect Cr 2 O 7 2− from aqueous water simultaneously ( Lin et al, 2017 ; Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…[6] U-IHEP-9 acts as a heterogeneous photocatalyst for CO 2 cycloaddition under the driving of visible light at room temperature. [7] Wang's group reported a uranyl MOC (metalorganic cage) based on a sulfur-containing bidentate carboxylic ligand, [8] which can effectively convert X-ray photons to electrical current signals and presents a promising sensitivity of 54.93 μC • Gy À 1 • cm À 2 .…”
Section: Introductionmentioning
confidence: 99%